Protoplast-Esculin Assay as a New Method to Assay Plant Sucrose Transporters: Characterization of AtSUC6 and AtSUC7 Sucrose Uptake Activity in Arabidopsis Col-0 Ecotype - Rottmann, Theresa M.; Fritz, Carolin; Lauter, Anja; Schneider, Sabine; Fischer, Cornelia; Danzberger, Nina; Dietrich, Petra; Sauer, Norbert; Stadler, Ruth (Frontiers in Plant Science, 2018)
The best characterized function of sucrose transporters of the SUC family in plants is the uptake of sucrose into the phloem for long-distance transport of photoassimilates. This important step is usually performed by one specific SUC in every species. However, plants possess small families of several different SUCs which are less well understood. Here we report on the characterization of AtSUC6 and AtSUC7, two members of the SUC family in Arabidopsis thaliana. Heterologous expression in yeast (Saccharomyces cerevisiae) revealed that AtSUC6Col-0 is a high-affinity H+-symporter that mediates the uptake of sucrose and maltose across the plasma membrane at exceptionally low pH values. Reporter gene analyses revealed a strong expression of AtSUC6Col-0 in reproductive tissues, where the protein product might contribute to sugar uptake into pollen tubes and synergid cells. A knockout of AtSUC6 did not interfere with vegetative development or reproduction, which points towards physiological redundancy of AtSUC6Col-0 with other sugar transporters. Reporter gene analyses showed that AtSUC7Col-0 is expressed in roots and pollen tubes and that this sink specific expression of AtSUC7Col-0 is regulated by intragenic regions. Transport activity of AtSUC7Col-0 could not be analyzed in baker’s yeast or Xenopus oocytes because the protein was not correctly targeted to the plasma membrane in both heterologous expression systems. Therefore, a novel approach to analyse sucrose transporters in planta was developed. Plasma membrane localized SUCs including AtSUC6Col-0 and also sucrose specific SWEETs were able to mediate transport of the fluorescent sucrose analogue esculin in transiently transformed mesophyll protoplasts. In contrast, AtSUC7Col-0 is not able to mediate esculin transport across the plasma membrane which implicates that AtSUC7Col-0 might be a non-functional pseudogene. The novel protoplast assay provides a useful tool for the quick and quantitative analysis of sucrose transporters in an in planta expression system.